Expression Analysis of Defense Related Genes in Rice Response to Bipolaris oryzae, the Causal Agent of Rice Brown Spot - Songkumarn, Pattavipha; Chaijuckam, Patcharavipa; Tongsri, Veeranee; Guerrero, Jonathan Jaime G. (Applied Science and Engineering Progress, 2019)
The rice defense mechanism was studied against Bipolaris oryzae, the rice brown spot fungus, in two Thai rice varieties, Khao Dawk Mali 105 (KDML 105) and Jao Hom Nin (JHN) (showing highest and lowest susceptibility to B. oryzae, respectively). The expression was evaluated of eight genes through real-time quantitative reverse transcription polymerase chain reaction. The gene involved in the salicylic acid (SA) signaling pathway (OsPAL) and the pathogenesis related genes (OsPR1b and OsPBZ1) were upregulated in both varieties with no significant differences. Despite higher expression of the genes involved in the jasmonic acid (JA) signaling pathway (OsLOX and OsAOS2) in JHN, the expression of JiOsPR10 was not significantly different in both varieties. The genes involved in the ethylene (ET) signaling pathway (OsACS1 and OsEIN2) were expressed more highly and far more rapidly in KDML 105 than JHN. Overall, our results demonstrated that the investigated genes related to SA, JA and ET defense pathways may not play a major role in rice resistance against B. oryzae. Furthermore, the high level of transcript accumulation of genes related to the ET signaling pathway may interfere with the ability of rice to resist B. oryzae. The study provided information for a better understanding of rice defense mechanisms against B. oryzae.